Modeling and development of haptics device for therapeutic gastrointestinal endoscopy - Sun, Zheng Long (2010)
Haptics can improve robotic surgery performance by providing force feedback to the surgeon. Its importance and necessity have been proved by many researchers as they look into providing force feedback to the robotic surgery system. Especially in the MIS(Minimally Invasive Surgery) and NIS (Non-invasive Surgery)robotic surgical system, it is essential to provide haptics information to the surgeon for a better performance. The goal is to let the surgeons feel as though they are directly opearating on the patient rather than having a robot mediate the interaction.